2018
DOI: 10.1002/cbic.201800634
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Extracellular Matrix Protein TapA Is a Two‐Domain Partially Disordered Protein

Abstract: Biofilms are aggregates of microbial cells that form on surfaces and at interfaces, and are encased in an extracellular matrix. In biofilms made by the soil bacterium Bacillus subtilis, the protein TapA mediates the assembly of the functional amyloid protein TasA into extracellular fibers, and it anchors these fibers to the cell surface. We used circular dichroism and NMR spectroscopy to show that, unlike the structured TasA, TapA is disordered. In addition, TapA is composed of two weakly interacting domains: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
4
14
0
Order By: Relevance
“…subtilis depends on the protein TapA, which has a role in promoting TasA stability and fibre formation in vivo (Branda et al, 2006;Romero et al, 2010;Romero et al, 2014;Abbasi et al, 2019;El Mammeri et al, 2019 Figure 3f) and recent NMR analysis has suggested that the C-terminus of TapA is a disordered protein, while the N-terminus is a structured domain, with the two domains interacting with lipid vesicles in a co-operative manner (Abbasi et al, 2019). Collectively, our immunoblot and genetic data support the conclusion that TapA is cleaved at two positions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…subtilis depends on the protein TapA, which has a role in promoting TasA stability and fibre formation in vivo (Branda et al, 2006;Romero et al, 2010;Romero et al, 2014;Abbasi et al, 2019;El Mammeri et al, 2019 Figure 3f) and recent NMR analysis has suggested that the C-terminus of TapA is a disordered protein, while the N-terminus is a structured domain, with the two domains interacting with lipid vesicles in a co-operative manner (Abbasi et al, 2019). Collectively, our immunoblot and genetic data support the conclusion that TapA is cleaved at two positions.…”
Section: Discussionsupporting
confidence: 85%
“…TapA is described as an accessory protein that is thought to be needed for the formation of TasA fibres (Romero et al ., 2010; Romero et al ., 2011), and more specifically, for the attachment of the TasA fibres to the cell surface. Secondary structure analysis revealed TapA to be a two‐domain protein with significant regions of disorder (Abbasi et al ., 2019). Additionally TapA has recently been shown to form fibres (El Mammeri et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This observation is consistent with the recent report which described TapA to be composed of two interacting domains; a disordered C-terminal domain and a more structured N-terminal domain(Abbasi et al, 2018). Noticeably, the two-domain composition of TapA has been suggested to be important for its interactions in the extracellular matrix in biofilms(Abbasi et al, 2018).…”
Section: Resultssupporting
confidence: 93%
“…In the case of TapA 223 , the disordered region spreads in form of a single stretch from amino acid residues 200-251 (Supplementary Fig S2A & S2B). Again, these results were consistent with the report describing the disordered domain close to C-terminus in case of TapA(Abbasi et al, 2018).…”
Section: Resultssupporting
confidence: 93%
“…Indeed, our results are supported by evidence that TasA can preferentially interact with model bacterial membranes, which affects fiber assembly 83 , and that TasA fibers are located and attached to the cell surface via a proposed interaction with TapA, which forms foci that seem to be present on the cell wall 76 . Interestingly, TapA has been recently characterized as a two-domain, partially disordered protein 84 . Disordered domains can be flexible enough to interact with multiple partners 85, 86 , suggesting a similar mechanism for TapA: the N-terminal domain might be involved in the interaction with other protein partners, whereas the C-terminal disordered domain might anchor the protein to the cell surface.…”
Section: Discussionmentioning
confidence: 99%